Effect of the triterpene 3β, 6β, 16β-trihydroxylup-20(29)-ene isolated from the leaves of Combretum leprosum Mart. on cutaneous wounds in mice. (2nd August 2015) - Nascimento-Neto, Luiz Gonzaga do; Evaristo, Francisco Flávio Vasconcelos; Alves, Mayara Freire de Alencar; Albuquerque, Maria Rose Jane Ribeiro; Santos, Helcio Silva dos; Bandeira, Paulo Nogueira; Arruda, Francisco Vassiliepe Sousa; Teixeira, Edson Holanda
Abstract: Ethnopharmacological relevance: Combretum leprosum Mart. is a native species of the Caatinga, an important biome in the Brazilian semi-arid region. This species is commonly used in Brazil as a healing agent, as well as for the treatment of skin diseases. Aim of the study: This study investigated the healing potential of the ethanolic extract (EECL) and the bioactive triterpene 3β, 6β, 16β-trihydroxylup-20 (29)-ene (CLF-1) isolated from the leaves of C. leprosum . Materials and methods: Skin wounds (1 cm 2 ) were created in the dorsal zone of mice with a scalpel blade number 15. The treatment consisted in a daily topical application of 100 μl of 150 mM NaCl, EECL and CLF-1 (at 10 μg/100 μl) for 12 days. The lesions were then macro and microscopically evaluated. Results: On postoperative day (POD) 2, the lesions treated with EECL and CLF-1 showed a moderate presence of vessels of the granulation tissue progressing in the dermis. The same effect was not observed in the control group. The treatment with EECL and CLF-1 stimulated angiogenesis, resulting in a rapid deposition of extracellular matrix (ECM). Moreover, the animals treated with EECL and CLF-1 showed smaller lesions on POD 7, primarily due to the contraction in the reticular dermis induced by organization of myofibroblasts, which was not observed in the group treated with NaCl. In addition, the lesions treated with EECL and CLF-1 showed ECM restructuration and presence of epithelium coating, which was not observed in the group treated with NaCl, in which the lesions showed no epithelial lining, suggesting delayed healing. Conclusion: CLF-1 isolated from the leaves of C. leprosum may be considered to be an important molecule for the treatment of skin lesions. However, further investigations are necessary to establish its role in chronic lesions and to elucidate the mechanism of action involved in the cutaneous healing process. To the best of our knowledge, this is the first report describing the pro-healing activity of the ethanolic extract and the triterpene 3β, 6β, 16β-trihydroxylup-20(29)-ene isolated from leaves of C. leprosum . Graphical abstract: